Management of losses (thermalization-transmission) in the Si-QDs inside 3C–SiC to design an ultra-high-efficiency solar cell. (April 2020) - Heidarzadeh, Hamid; Rostami, Ali; Dolatyari, Mahboubeh
Abstract: Thermalization loss is one of the major losses in the single junction solar cells. Here, 3C–SiC as a wide bandgap semiconductor is used to manage this loss. To prevent the transmission of low energy photons, the intermediate bands inside the forbidden band gap is used. To do this, silicon quantum dots inside silicon carbide is suggested. At first, the detailed balance calculations are carried out to determine the efficiency limits of a cell with one and two mini-bands. Optical simulation using 3D FEM solution of the Schrodinger equation is done to obtain mini-bands, wave functions, and hence the optical absorption coefficient. Dimension parameters of a QD array like radius, inter-dot spacing, and array size are optimized to obtain a maximum efficiency. Inter-band and inter-sub-band absorption coefficient are calculated. That applied to determine the optimum characteristic of a QD–based intermediate band solar cell. The photocurrent increases as the inter-dot spaces decrease. Suitable radiuses and inter-dot spaces are found to obtain a high absorption coefficient and hence higher photocurrent. Finally, the effect of non-radiative recombination on the device performances is simulated. These results provide significant information to design a three-dimensional QDs based intermediate band solar cells.